Conversion of Industrial Food Wastes Cranberry Pomace into Foods Blending with Rice Flour Using Single-screw Extrusion Process - Mitra, Pranabendu; Khanvilkar, Sagar; Samudrala, Sai Kumar; Shroff, Kaushal Sunil (Journal of Food Industry, 2024)
The main objective of this study was to convert the cranberry pomace into value-added extruded cereals/snacks blending with rice flour using a single screw extruder based on the physicochemical properties of extrudates because utilization of the byproduct cranberry pomace would be necessary for the growth of cranberry juice processing industries and the extruded snacks/cereals with higher fiber and antioxidant and less carbohydrate would be required to fulfill the consumers’ demand. The six different formulations by blending 0, 5, 10, 15, 20 and 25% cranberry pomace with 100, 95, 90, 85, 80 and 75% of rice flour, respectively, were extruded using a single screw extruder. The temperature (150℃), screw speed (270 rpm), feed rate (20 Kg/hr) and feed moisture content (35%) were constant during extrusion. The physicochemical properties of the extrudates were characterized to determine the desirable formulations. The results indicated that radial expansion ratio (1.11-1.67), the solid density (0.71-0.76 g/mL), piece density (0.20-0.63 g/mL), porosity (14.49-72.38%), hardness (23-157.73 N), crispness (4.17-13.5), moisture content (3.22-4.39%), water activity (0.14-0.36) and the water solubility (7.07-30.80%) of rice flour and cranberry pomace blend extrudates were varied depending on the combinations of the rice flour and cranberry pomace. The results revealed that up to 20% cranberry pomace could be added with 75-80% rice flour to develop high fiber and antioxidant with less carbohydrate cereal/snack products. The utilization of cranberry pomace combining with rice flour through extrusion process can provide a unique opportunity to generate healthier snacks and cereals that have higher fiber and antioxidant and low carbohydrate.